Formulasi Sabun Mandi Padat Ekstrak Daun Jeruk Bali (Citrus Maxima Merr.) sebagai Antibakteri terhadap Staphyloccous aureus - Noela Riski Riani Sumbung; Vivin Nopiyanti; Siti Aisiyah; Reslely Harjanti (State University of Gorontalo, 2023)
Solid bath soap is one of the most common cosmetic preparations used by the public to clean the body from dirt. Grapefruit leaves contain flavonoids that are able to maintain healthy skin, and can inhibit the growth of bacteria. The purpose of this study was to formulate the leaf extract of grapefruit into a solid bath soap that has good physical and stability qualities and to determine its antibacterial effect against S. aureus. Grapefruit leaves were macerated with 96% ethanol solvent then the extract obtained was formulated into solid soap preparations with extract variations, namely 1; 3 and 5%. Furthermore, physical quality and stability tests have been carried out as well as testing the antibacterial activity of the bath soap preparations against S. aureus bacteria by agar diffusion method by means of wells. The final stage was statistical data analysis. The results showed that the solid bath soap preparations with grapefruit leaf extract had good physical quality and stability, the formulation of solid bath preparations with extract concentrations of 1%, 3%, and 5% had antibacterial activity with an average diameter of the inhibition zone against S. aureus bacteria were 5.6 mm, 7 mm and 10.8 mm, respectively, which were included in the moderate to strong category. The formulation with the addition of 5% extract had the most effective antibacterial activity with an average inhibition zone of 10.8 mm.